Bovine or Porcine: Does the Type of Surfactant Matter?. (29th February 2020) - Boshoff Coyles, Lize; Joolay, Yaseen; Tooke, Lloyd
Abstract: Background: Hyaline membrane disease contributes majorly to preterm mortality, particularly in the developing world. There are two animal-derived surfactants available in South Africa: poractant-alfa (120 mg/1.5 ml) and beractant (100 mg/4 ml). At equivalent doses, studies have shown no difference in mortality or morbidity, although there are limited data from the developing world. Both surfactants have been available for use at Groote Schuur Hospital in Cape Town but due to policy change, poractant-alfa was no longer available from November 2014. Due to weight-based dosing charts, infants who were given poractant-alfa received 20% higher dosages of phospholipid. Methods: A before-and-after policy change non-experimental study was performed including infants from 2013 to 2015. Infants weighing <1500 g were recruited by identifying them from the surfactant register and further data were obtained from patient records. Data fields included infant weight, gestation, respiratory support and outcomes. Results: Two hundred and eight infants were included. One hundred and eight received beractant and 100 received poractant-alfa. The mean birth weight was 1031 g and gestational age 28.8 weeks. Seventy-nine percent of the infants received surfactant via the INSURE (intubation, surfactant and extubation) method. The combined outcome for death or bronchopulmonary dysplasia was 35.3% in the beractant group and 36% in the poractant-alfa group ( p = 0.902). All secondary outcomes including neonatal morbidities, oxygen at 28 days or length of ventilation were not statistically significant. Conclusion: There were no significant differences in outcomes between the two groups of infants who received different surfactants at the dosages used in our unit. This is one of the few studies of this type performed in a low- and middle-income countries.